Beberapa Karakteristik Kerupuk Ikan yang Dibuat Dengan Variasi Rasio Ikan Nila:Tapioka dan Lama Perebusan Adonan - Agus Pamudji Rahardjo; Haryadi Haryadi (agriTECH, 1997)
'Keropok' crackers preparation was varied in the ratio of fish added to tapioca starch, and the length of dough-like mixture cooking. The fish used was in the form of ground red 'nila' fish (Orcochromis niloticus) meat. The ratios of fish to starch were 30:70, 40:60, 50:50, and 60:40. The ground fish and starch and other ingredients were mixed to get dough-like mixture which was then stuffed into a plastic bag having 5 cm diameter and 20 cm length. The stuffed rolls were then cooked in boiling water for 45, 60 and 75 min, cooled immediately, sliced, and dried. The crackers were analyzed for moisture, and charac-terized for thermal properties, acceptability, objective texture , degree of expansion, and hygroscopicity. The results indicated that higher ratio of fish to starch needed higher energy to melt. Higher ratio of fish to starch gave lower `keropok' cracker acceptability. Higher ratio and longer cooking time resulted in decrease in the degree of expansion during frying. However, any samples showed no difference in hygroscopicity. The crackers expanded well during frying when the initial moisture content ranged from 8,53 to 11,19%. Hardness of the acceptable fish crackers were 31,24 - 40,77 N. Based on the high acceptability, and economic reason relating to lower ratio of fish to tapioca starch and shorter cooking time, methods of preparation involving addition of fish to starch at ratio 30:70 and dough-like cooking for 60 min and at ratio 40 : 60 and cooking for 45 min were considered best.